Order in early Chinese excavated texts natural, supernatural, and legal approaches - Wang, Zhongjiang 1957- (Palgrave Macmillan, 2016)
"Recently discovered ancient silk and bamboo manuscripts have transformed our understanding of classical Chinese thought. In this book, Wang Zhongjiang closely examines these texts, and by parsing the complex divergence between ancient and modern Chinese records reveals early Chinese philosophy to be much richer and more complex than we ever imagined. As numerous and varied cosmologies sprang up in this cradle of civilization, beliefs in the predictable movements of nature merged with faith in gods and their divine punishments. Slowly, powerful spirits and gods were stripped of their potency as nature's constant order awakened people to the possibility of universal laws, and from those laws was finally born an ideally conceived community, objectively managed, and rationally ordered"--